2006
DOI: 10.1113/jphysiol.2006.108779
|View full text |Cite
|
Sign up to set email alerts
|

The role of adenosine in the early respiratory and cardiovascular changes evoked by chronic hypoxia in the rat

Abstract: Experiments were performed on anaesthetized normoxic (N) rats and chronically hypoxic rats that had been exposed to 12% O 2 for 1, 3 or 7 days (1, 3 or 7CH rats). The adenosine A 1 receptor antagonist DPCPX did not affect the resting hyperventilation of 1-7CH rats breathing 12% O 2 and increased resting heart rate (HR) in 1CH rats only. DPCPX partially restored the decreased baseline arterial pressure (ABP) and increased femoral vascular conductance (FVC) of 1 and 3CH rats, but had no effect in N or 7CH rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
(120 reference statements)
0
12
0
1
Order By: Relevance
“…Exogenously applied adenosine increased CSN chemosensory discharges in the cat in vivo (24, 25) and in vitro (38), as well as in the rat (43). Adenosine and its analogs have been shown to stimulate ventilation in a dose-dependent manner in several species, including humans and rats (26,37,40,45,46), with the stimulatory effect reaching up to nearly 60% of the maximal asphyxic ventilation; this stimulation is abolished by CSN section and mediated by A 2 receptors (26; see 8). The physiological meaning of these pharmacological findings on CSN and ventilation became obvious when it was demonstrated that mild hypoxia augments adenosine release in an in vitro preparation of rat CB (2).…”
mentioning
confidence: 99%
“…Exogenously applied adenosine increased CSN chemosensory discharges in the cat in vivo (24, 25) and in vitro (38), as well as in the rat (43). Adenosine and its analogs have been shown to stimulate ventilation in a dose-dependent manner in several species, including humans and rats (26,37,40,45,46), with the stimulatory effect reaching up to nearly 60% of the maximal asphyxic ventilation; this stimulation is abolished by CSN section and mediated by A 2 receptors (26; see 8). The physiological meaning of these pharmacological findings on CSN and ventilation became obvious when it was demonstrated that mild hypoxia augments adenosine release in an in vitro preparation of rat CB (2).…”
mentioning
confidence: 99%
“…Adenosine receptor antagonists differently affected the response of the respiratory system to acute and chronic hypoxia and hypercapnia [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Adenosine, a product of degradation of macroergic compounds formed during brain hypoxia, acts as a tonic neuromodulator of respiration and may produce various effects depending on the site of its action and type of adenosine receptors to be activated [6,13]. The purinergic system considerably modulates respiration in not only fetuses and newborns [4], but also adults [7].…”
mentioning
confidence: 99%
“…Interestingly, a nonspecific Ado receptor antagonist [8-(psulfophenyl)theophylline hydrate] was shown to blunt the increase in respiratory frequency elicited by acute hypoxia in CHox rats (56). Walsh et al (56) concluded that the increased HVR in CHox rats was due to activation of A 2 receptors by endogenous Ado released in the CB.…”
mentioning
confidence: 97%
“…Walsh et al (56) concluded that the increased HVR in CHox rats was due to activation of A 2 receptors by endogenous Ado released in the CB. Moreover, Ado A 2a and A 2b receptors are expressed in CB type I cells (10,17), and Ado signaling contributes to chemoexcitation via presynaptic and postsynaptic mechanisms involving A 2 receptors (9).…”
mentioning
confidence: 98%